EDUKASI DAN BIMBINGAN TEKNIS TEKNOLOGI AKUAPONIK SISTEM RAKIT APUNG GUNA MENINGKATKAN PRODUKTIVITAS BUDIDAYA IKAN LELE UD. SONIA RATU - Zahtul, Rafi; Saputra, Fazril; Ayuni, Fenika; Martisa, Irna; Islama, Dini; Ibrahim, Yusran; Samuki, Khairul; Hendri, Afrizal (Universitas Mataram, 2024)
Meureubo District has the potential for freshwater aquaculture to be developed. UD Sonia Ratu is a fish cultivation business that focuses on raising catfish seeds. This fish cultivation business still relies on conventional cultivation systems so that cultivation productivity is not optimal. Increasing the productivity of fish farming can be done by utilizing floating raft system aquaponics technology. Floating raft system aquaponics technology is a cultivation activity that combines fish cultivation with plants. The aim of this service is to introduce floating raft aquaponics technology for catfish farmers in Meureubo District so that they can increase the productivity of UD Sonia Ratu's catfish cultivation business. The method for implementing this activity is to provide direct education and technical guidance regarding the techniques for making floating raft aquaponic systems. The material presented in educational activities includes benefits, how to make it, concept of use and direct practice of making and directly applying aquaponics. The result of this activity is that UD Sonia Ratu fish farmers gain an understanding of cultivation methods using floating raft system aquaponic technology. Increased understanding of fish farmers by 35% based on the results of tests that have been carried out. Fish farmers gain skills in how to make aquaponics and apply aquaponics systems directly to fish farming ponds. The conclusion of this activity is an increase in the understanding and skills of UD Sonia Ratu's fish cultivation business regarding cultivation methods using the floating raft aquaponics system